Putting context at the forefront: a critical case study of journalists’ layoffs in Mexico (Communication & Society, 2023)
At a time of crisis in news media organizations, with changes in the world of work occurring in different regions, a significant number of newsrooms have been affected by the mass firing of journalists. Multiple layoffs can be understood as part of a broader process of organizational change that is linked to deterioration in the working conditions of media workers and a transformation of journalistic modes of production. To understand the processes of organizational change in news organizations with multiple layoffs, this critical case study of news organizations in a western Mexican city relied on the analysis of data from multiple sources of information. It was found that the processes deriving in multiple layoffs do not develop homogeneously, but take shape according to context-specific characteristics such as, in the Mexican case, the institutional fragility of journalism and the uneven protection of rights across the territory. The collected data set illustrates how the processes of downsizing, convergence and precarization âŽ¼commonly studied separatelyâŽ¼ may occur simultaneously and in an integrated fashion. Specific interplays of global and local trends found in this case study include pressure from governments and lack of tools for claiming labor rights.